Enhancing teaching skills and leveraging good assessment and feedback practices to facilitate inclusion in blended learning environments - Ιωαννίδη Βασιλική; Μαλαφάντης Κωνσταντίνος; Σούλης Σπυρίδων-Γεώργιος (Education Sciences, 2024)
The purpose of this paper is to present a conceptual and applied framework regarding educational evaluation from the perspective of inclusive learning in the mixed classes of the 21st century. The literature review highlights the relationship of inclusion and assessment and points to important issues of contemporary pedagogical practice, such as Universal Design for Learning, multimedia and accessible educational materials and Differentiated Instruction. The work contributes to Inclusive education by enhancing teaching skills and analyzing assessment and feedback approaches, which can be integrated into all teaching to support the engagement of teachers and learners in all educational contexts and especially in blended inclusive learning environments.